Analisis Strategi Pengelolaan Kualitas Kehidupan Kerja Dalam Meningkatkan Kinerja Karyawan UD. ZIDAN COLLECTION TAYU-PATI - Martini, Tina; Astuti, Windy Vinorika Yuli (BISNIS, 2017)
This study aims to analyze the strategy of quality management of UD working life. Zidan Collection in improving employee performance and what factors become supporters and obstacles in improving the performance of UD employees. Zidan Collection. This research includes field research and case study with descriptive qualitative approach. Primary data sources are sourced from direct interviews with UD convection leaders and employees. Zidan Collection, while secondary sources are obtained through documents owned by UD. Zidan Collection. Data collection techniques in this study are interviews, observation and documentation. Data analysis techniques with data reduction, data presentation and conclusion drawing. Test the credibility of the data with extension of observation, increasing perseverance, and triangulation. This research resulted that, firstly strategy of quality management of UD working life. Zidan Collection in improving the performance of employees is done through the development of quality aspects of work life, namely: open interactive communication, employee involvement in conflict resolution through deliberation, career development by providing training, employment participation by involving all employees in the meeting, build employees pride with undertake recreation once a year and provide THR, appropriate compensation by awarding bonuses to achievers, environmental safety by providing a clean, safe and comfortable working environment with workplace music, work safety by making all employees as permanent employees, as well as occupational health given in the form of including all employees as members of BPJS employment. Second, the factors that become supporters in improving the performance of UD employees. Zidan Collection is the provision of bonuses to employees, the existence of insurance for employees, and the availability of facilities that support employee comfort in work. While the inhibiting factor is the level of employee education is still low and most employees are housewives.